The Effect of Price Perception and E-Wom on Purchase Decisions on the E-Commerce Platfrom Shopee - Elang Handika Kartawinata; Mohamad Ikbal Santoso; Yusuf Yusuf; Soesanty Maulany (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Purchasing behavior in the digital marketplace is shaped by several variables, notably consumers' perceptions of price and the influence of Electronic Word of Mouth (e-WOM). This research investigates the extent to which these two factors—price perception and e-WOM—affect consumer purchasing decisions on the Shopee platform, both individually and collectively. Employing a quantitative approach through structured surveys distributed to active Shopee users, this study applies multiple linear regression analysis to evaluate the relationships between the independent variables (price perception and e-WOM) and the dependent variable (purchase decisions). The findings demonstrate that both variables significantly and positively influence consumer purchasing behavior. The results underscore the importance of competitive pricing strategies and the strategic use of e-WOM in enhancing consumer engagement and driving sales performance on e-commerce platforms.